2016
DOI: 10.1002/admi.201600284
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Surface Hydrophobicity and Polarizability of Fluorinated Dielectrics for Organic Field‐Effect Transistors with Excellent Gate‐Bias Stability and Mobility

Abstract: It is demonstrated that treating dielectrics with fluorinated polymers, which have excellent hydrophobicity, chemical inertness, and the lowest polarizability, yields a semiconductor‐compatible surface energy and excellent charge detrapping characteristics. Fluorocopolymers, polystyrene‐random‐poly(2,3,4,5,6‐pentafluorostyrene) (PS‐r‐PPFS) copolymers with different 2,3,4,5,6‐pentafluorostyrene (PFS) loadings, are synthesized to modify a SiO2 gate dielectric using radical polymerization. Surface energy (γ) of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…In this case and highlighted in Figure 8, the increase in the content of PFS reduces the V T , while having little effect on the µ, which is consistent with what we would expect for the addition of fluorinated dielectrics [52]. This suggests that the PFS molecules present on the dielectric surface reduce the concentration of charge trap sites at the semiconductor/dielectric interface [11,12]. For the PFS/MMA copolymers with a PFS composition greater than F PFS = 0.57 , there were few functioning devices, and the results were unreliable with large deviations.…”
Section: Poly(pfs-ran-mma) Copolymers As Dielectric Materials In Orgasupporting
confidence: 85%
See 1 more Smart Citation
“…In this case and highlighted in Figure 8, the increase in the content of PFS reduces the V T , while having little effect on the µ, which is consistent with what we would expect for the addition of fluorinated dielectrics [52]. This suggests that the PFS molecules present on the dielectric surface reduce the concentration of charge trap sites at the semiconductor/dielectric interface [11,12]. For the PFS/MMA copolymers with a PFS composition greater than F PFS = 0.57 , there were few functioning devices, and the results were unreliable with large deviations.…”
Section: Poly(pfs-ran-mma) Copolymers As Dielectric Materials In Orgasupporting
confidence: 85%
“…Park et al demonstrated that using poly(PFS) as an interlayer in bottom-gate top-contact pentacene-based transistors improved gate-bias stability [11]. Jang et al used poly(styrene-random-PFS) copolymers to control the dielectric surface energy for high performing OTFTs [12]. The authors reported decreases in field-effect mobility, as the difference in interfacial energy between the dielectric surface and pentacene semiconductor increased.…”
Section: Introductionmentioning
confidence: 99%
“…The surface energies γ L were calculated using the Owens–Wendt model as follows where θ is the contact angle of the test liquid with the sample; γ L N and γ L P are the nonpolar and polar components of the test liquid, respectively; and γ S N and γ S P are the nonpolar and polar components of the surface energy of the sample, respectively. The calculated surface energy of the 5F-SAPMA film (37.31 mJ/m 2 ) was lower than that of the PhAPMA film (48.15 mJ/m 2 ), indicating that the 5F-SAPMA film surface was more hydrophobic than the PhAPMA film surface because of the fluorinated functional unit in the 5F-SAPMA. , Next, the AFM images (1.0 μm × 1.0 μm) of the PhAPMA and 5F-SAPMA films, shown in Figure c,d, respectively, were captured to estimate the root-mean-square (RMS) surface roughness. The RMS surface roughness of the PhAPMA film (3.18 Å) was negligibly lower than that of the 5F-SAPMA film (3.40 Å).…”
Section: Resultsmentioning
confidence: 93%
“…The calculated surface energy of the 5F-SAPMA film (37.31 mJ/ m 2 ) was lower than that of the PhAPMA film (48.15 mJ/m 2 ), indicating that the 5F-SAPMA film surface was more hydrophobic than the PhAPMA film surface because of the fluorinated functional unit in the 5F-SAPMA. 37,38 Next, the AFM images (1.0 μm × 1.0 μm) of the PhAPMA and 5F-SAPMA films, shown in Figure 2c,d, respectively, were captured to estimate the root-mean-square (RMS) surface roughness. The RMS surface roughness of the PhAPMA film (3.18 Å) was negligibly lower than that of the 5F-SAPMA film (3.40 Å).…”
Section: ■ Resultsmentioning
confidence: 99%
“…In addition to surface roughness, the surface energy or hydrophobicity, surface glass transition temperature ( T g ), and phase separation of a blended polymer dielectric also have significant influence on the semiconductor morphology. , The effect of surface energy on semiconductor grain growth has been recognized. However, the direct relationship between surface energy and semiconductor performance is still under debate due to the difference in semiconductor types and fabrication methods, and the complexity of how grain size and boundaries can impact charge transport.…”
Section: Requirements For Of Polymer Materials As Gate Dielectricsmentioning
confidence: 99%